EVOLUSI MORFOSINTAKTIKOPRAGMATIS KATA DALAM BAHASA INDONESIAEVOLUSI MORFOSINTAKTIKOPRAGMATIS KATA DALAM BAHASA INDONESIA - Astini, Edi (Lembaran Ilmu Kependidikan, 2008)
Language is not static. It undergoes evolution in all aspects: meaning, structure, and use. Nowadays Indonesian language develops in an unregular way. The research intended to detect the change of some words which are frequently used but seems in another way as before. As method, it adopted the qualitative approach and used the theory of syntax, morphology, and pragmatics as reference to analyse the data. The data was gathered from televison and newspapers, in the form of words, clauses, or phrases.The respondents were a group of people in the domain of education, administration, dan arts. To analyse their input, the cross-check between it and those of two experts in Indonesian language has been made. As reference, we used dictionnaries, grammar books, and pragmatic books. The result showed that about 15 words undergo evolution and need attention from Pusat Bahasa. The institute should decide whether the changes should be legalized or itÃ¢â¬â¢s the teaching of Indonesian language which must be improved. Kata kunci: evolusi, morfologi, sintaksis, pragmatik